"Finger‐Flapping" Hand Stereotypy as a Presenting Feature of Wilson's Disease. Issue 1 (8th November 2018) - Bhatti, Amit; Jain, Neeraj; Desai, Karan; Ravat, Sangeeta H.; Agarwal, Pankaj A.
Abstract : View Supplementary Video 1